The Hadiths Referred by Ahmed Hâşi̇mzâde in the Work Titled Tefsîru’lkur’ânî’l-azim and Their Evaluation in Terms of Validity - Kazimova, Roya (Scholarya Demo Journal of Ruby, 2021)
The valuable scholar Ahmed Haşimzâde, who devoted his life to education, has written the work of Tefsiru’l-Kur’ani’l-Azim, as a result of his scientific accumulation of more than sixty years, by facing all the difficulties of his era. This study is the third tafsir containing all the surahs of the Quran written in the Azerbaijani language. Due to the scarcity of Arabic and Persian words, its plain language and fluent style, which can be easily understood by everyone even today, are among the main features of tafsir (interpretation of Quran). The Tafsîru’l-Kur’ani’l-Azîm tafsir, which aims the ordinary citizen to learn her religion correctly, is a manuscript. It’s publishing in the Arabic and Latin alphabet as a work of fidelity to the commentator will have a great impact on both its status as a rightful owner and the realization of its intended purpose. In this study, it is aimed to criticize the authenticity of the hadiths in Haşimzâde’s commentary on Tefsîru’l-Kur’ânî’l-Azîm. He has given great importance to the method of interpreting the Quran with the Sunnah. Hadiths are frequently encountered in the explanations of the Quranic verses. While the majority of these narrations were authentic hadiths, the author mentioned also hasan and weak hadiths. Made-up hadiths have been given very little space. The publications created in recent times, such as Tafsîru’l-Kur’ânî’l-Azîm, have made significant contributions to the correct understanding of the Quran, which is now prevalent. It is also critical in combating the currents that believe the Quran is adequate and ignores the prophethood of Muhammad (pbuh).